A Tale of Three SENCOS, post 2015 Reforms. Issue 4 (23rd January 2019) - Whalley, Sara
Abstract: This article forms part of a Masters Inclusive Education research project. Whilst most inclusive research focuses on a marginalised group, my research participants would not normally be deemed marginalised. Nevertheless, they have a pivotal role within the English mainstream education system to promote inclusive practice, improving outcomes for the most vulnerable young people. For this reason, I intend to explore the role of three Special Educational Needs Co‐ordinators (SENCOs) post 2015 reforms and firmly believe this is fundamentally inclusive research.